EFEKTIVITAS SUPLEMEN OMEGA-3 TERHADAP KADAR GLUKOSA DARAH PUASA TIKUS GALUR WISTAR(Rattus norvegicus) YANG DIINDUKSI ALOKSAN - Bianca Khairunnisah Desvany (2021)
Diabetes mellitus (DM) requires special attention because the total sufferer continues to increase from year to year. Indonesia is ranked the 7th country with the highest number of DM in 2019. Because of the high prevalence, it is necessary to find alternative treatments that are more effective, one of which is omega-3 suplemments which is antihyperglycemic. This study aims to determine the effectiveness of omega-3 suplemments on decreasing fasting blood glucose (KGDP) levels in alloxan-induced white male Wistar rats. Samples were 30 male rats, aged 2-3 month, weight 150-200 grams. Rats were grouped into 6 groups with (K1) as normal control, (K2) group with alloxan, (K3) group with alloxan and glibenclamide, (P1) group of alloxan and omega-3 supplements at a dose 36 mg/kg, (P2) group of alloxan and omega-3 supplements at a dose 72 mg/kg, and (P3) group of alloxan and omega-3 supplements at a dose 144 mg/kg. Giving omega-3 suplemments was given for 7 days orally and then KGDP was assessed from blood taken from the rats using a glucometer. Kruskal-Wallis test, there was an effectiveness of omega-3 supplements on reducing KGDP (p = 0.001). The Mann-Whitney test showed there was no control difference between the positive group and the second group (P2) because it had the same effect, so it could be denied that offering omega-3 supplements at a dose of 72 mg / kgBW was the best in reducing KGDP (p = 0.117) because omega-3 can increase adiponectin levels which have an impact on increasing insulin sensitivity.